Development of Banana Kepok Starch Extract (Musa Pardisia) and Moringa Leaves (Moringa oleifera Lamk.) As An Adolescent Prebiotic Supplement - Luthfiyah, Fifi; Ikayanti, Retno; Iswarawanti, Dwi Nastiti (Pelopor Publikasi Akademika, 2024)
The study aimed to determine the feasibility of kepok banana starch, Moringa leaf powder, to meet microbiological requirements as a high fe-resistant starch supplement Methode. This type of research is experimental research. The study was conducted in two stages. The first stage determines the formulation of resistant starch extract supplements to which Moringa leaf powder is added. The second stage determines the composition of vitamin C levels, fiber content, and chemical composition of the product. The third stage analyzes the product stability test by differentiating products based on storage duration and storage temperature. In this study, the type of banana used was the red kepok banana which calculated water extraction. Results: 6,679 kg of fresh kepok bananas produced 840 g of resistant starch. The yield of the material is 14.97%. 1,580 kg of fresh Moringa leaves produce 587 grams of Moringa leaf powder. material yield of 37.15%. The use of the calculated supplement is 11 grams of banana starch extract mixed with 0.5 grams of Moringa powder. The results of the microbiological examination that has been carried out on product samples show that the product is free and safe from E-coli, Staphylococcus, and Salmonella thypi bacteria and has met the microbiological quality requirements for health supplement products. Conclusion: There are three microbiological examinations that have been carried out on product samples, namely Salmonella Sp, E-Colli, and Staphylococcus Aureus, and have met the microbiological quality requirements of health supplement products.